Bioavailability and mobility of organic contaminants in soil: new three-step ecotoxicological evaluation - Prokop, Zbyněk; Nečasová, Anežka; Klánová, Jana; Čupr, Pavel (Environmental science and pollution research international, 2016)
A novel approach was developed for rapid assessment of bioavailability and potential mobility of contaminants in soil. The response of the same test organism to the organic extract, water extract and solid phase of soil was recorded and compared. This approach was designed to give an initial estimate of the total organic toxicity (response to organic extractable fraction), as well as the mobile (response to water extract) and bioavailable fraction (response to solid phase) of soil samples. Eighteen soil samples with different levels of pollution and content of organic carbon were selected to validate the novel three-step ecotoxicological evaluation approach. All samples were chemically analysed for priority contaminants, including aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs), hexachlorocyclohexane (HCH) and dichlordiphenyltrichloroethane (DDT). The ecotoxicological evaluation involved determination of toxicity of the organic, mobile and bioavailable fractions of soil to the test organism, bacterium Bacillus cereus. We found a good correlation between the chemical analysis and the toxicity of organic extract. The low toxicity of water extracts indicated low water solubility, and thus, low potential mobility of toxic contaminants present in the soil samples. The toxicity of the bioavailable fraction was significantly greater than the toxicity of water-soluble (mobile) fraction of the contaminants as deduced from comparing untreated samples and water extracts. The bioavailability of the contaminants decreased with increasing concentrations of organic carbon in evaluated soil samples. In conclusion, the three-step ecotoxicological evaluation utilised in this study can give a quick insight into soil contamination in context with bioavailability and mobility of the contaminants present. This information can be useful for hazard identification and risk assessment of soil-associated contaminants. Graphical Abstract New three-step ecotoxicological evaluation by using the same organism.
Keywords: Risk identification/assessment; ekotoxikologie; látky znečišťující půdu; biologická dostupnost; Ecotoxicological evaluation; Biodegradation, Environmental; biodegradace; Risk Assessment; polycyklické aromatické uhlovodíky; půda; Soil contamination; Soil Pollutants; Bioavailability; hodnocení rizik; Soil; Polycyclic Aromatic Hydrocarbons; Toxicity; chlorované uhlovodíky; Bacillus cereus; Hydrocarbons, Chlorinated; Mobility; Bioremediation; Ecotoxicology; Biological Availability